(Mis)Matches in Translation – A Case Study of “The Big Fat Giant” and its Albanian Version - Qafzezi, Eriola (Vertimo studijos, 2018)
[full article, abstract in English; abstract in Lithuanian] The aim of this article is to observe how semantic peculiarities travel across languages and cultures. The original book, The Big Fat Giant, by Roald Dahl lends itself perfectly to such a comparative study due to its linguistic and semantic features that need to be explored in order to understand how they were brought to the Albanian language and culture. Classifications of several levels at which mismatches occur are mentioned, such as mismatches at the level of syntax, semantics and phonetics. Examples are given to illustrate each level. The discussion is enriched with observations and examples from the intertextual level. The paper concludes with findings which refer to this tale in particular and recommendations for further research.